Modular allylation of C(sp3)–H bonds by combining decatungstate photocatalysis and HWE olefination in flow. Issue 24 (9th June 2022) - Capaldo, Luca; Bonciolini, Stefano; Pulcinella, Antonio; Nuño, Manuel; Noël, Timothy
Abstract : We report a flow platform for the modular allylation of strong aliphatic C(sp 3 )–H bonds based on the merger of photocatalytic HAT and a HWE reaction. This approach enables both early- and late-stage diversification of various hydroalkanes. Abstract : The late-stage introduction of allyl groups provides an opportunity to synthetic organic chemists for subsequent diversification, furnishing a rapid access to new chemical space. Here, we report the development of a modular synthetic sequence for the allylation of strong aliphatic C(sp 3 )–H bonds. Our sequence features the merger of two distinct steps to accomplish this goal, including a photocatalytic Hydrogen Atom Transfer and an ensuing Horner–Wadsworth–Emmons (HWE) reaction. This practical protocol enables the modular and scalable allylation of valuable building blocks and has been applied to structurally complex molecules.